2019
DOI: 10.1088/2040-8986/aafe61
|View full text |Cite
|
Sign up to set email alerts
|

Atom localization using Laguerre–Gaussian beams

Abstract: Use of the Laguerre-Gaussian fields in an atom-light interaction makes the linewidth of the optical spectrum narrow. We exploit this fact for providing the ability to accomplish simultaneous ultra-high precision and spatial resolution atom localization in a double-Λ atomic system; Under multi-photon resonance condition, the resolution of the localization is remarkably improved so that the atom can be localized in a region smaller than λ/20 × λ/20. Most prominently, the probability of finding the atom at a part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…We then consider configurations in which two of driving fields have LG profiles. First, we investigate the situation that two control fields, g It may be of interest to note that a similar term to that obtained in this work, i.e., Im[i e iφ0 g 42 g * 32 ] was the subject of another investigation in an atomic system, as has recently reported by the present authors and their colleague [50]. It was found that utilizing two control vortex beams with equal azimuthal indices, l 42 =l 32 , can permit ultra-high precision and spatial resolution atom localization.…”
Section: Resultssupporting
confidence: 56%
“…We then consider configurations in which two of driving fields have LG profiles. First, we investigate the situation that two control fields, g It may be of interest to note that a similar term to that obtained in this work, i.e., Im[i e iφ0 g 42 g * 32 ] was the subject of another investigation in an atomic system, as has recently reported by the present authors and their colleague [50]. It was found that utilizing two control vortex beams with equal azimuthal indices, l 42 =l 32 , can permit ultra-high precision and spatial resolution atom localization.…”
Section: Resultssupporting
confidence: 56%
“…LG beam is a form of vortex beam with a helical phase structure and a doughnut-like intensity profile. This beam has recently been employed to narrow the Doppler line-shapes 31 , atom localization 32 , and spatially dependent atom-photon entanglement 33 . Such a beam was also exercised for generating entanglement of the orbital angular momentum states of photons 34 , quantum cryptography 35 , and a free-space quantum key distribution mechanism 36 .…”
Section: Introductionmentioning
confidence: 99%
“…LG beam is a form of vortex beam with a helical phase structure and a doughnutlike intensity profile. This beam has recently been employed to narrow the Doppler line-shapes [31], atom localization [32], and spatially dependent atom-photon entanglement [33]. Such a beam was also exercised for generating entanglement of the orbital angular momentum states of photons [34], quantum cryptography [35], and a free-space quantum key distribution mechanism [36].…”
Section: Introductionmentioning
confidence: 99%